2016
DOI: 10.1016/j.ymgmr.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The neurobehavioral phenotype in mucopolysaccharidosis Type IIIB: An exploratory study

Abstract: ObjectivesOur goal was to describe the neurobehavioral phenotype in mucopolysaccharidosis Type IIIB (MPS IIIB). Parents report that behavioral abnormalities are a major problem in MPS III posing serious challenges to parenting and quality-of-life for both patient and parent. Our previous research on MPS IIIA identified autistic symptoms, and a Klüver-Bucy-type syndrome as indicated by reduced startle and loss of fear associated with amygdala atrophy. We hypothesized that MPS IIIB would manifest similar attribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 36 publications
(46 reference statements)
1
35
0
Order By: Relevance
“…As pointed out by Potegal et al 4 and Shapiro et al, 5 MPSIII is the first inherited pediatric disease presenting systematically with clinical features of KBS.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…As pointed out by Potegal et al 4 and Shapiro et al, 5 MPSIII is the first inherited pediatric disease presenting systematically with clinical features of KBS.…”
Section: Discussionmentioning
confidence: 90%
“…In adults KBS may result from amyotrophic lateral sclerosis, 11 bilateral temporal lobectomy, 2 adrenoleukodystrophy, 12 Alzheimer`s disease, 13 herpes encephalitis, 14 and rapid correction of hyponatremia. 2 In children KBS has been observed after herpes encephalitis, 15 hypoxic insult, 16 in neuronal ceroid-lipofuscinosis, 17 MPSIIIA, 4 MPSIIIB, 5 and as a result of congenital bilateral anterior temporal malformation of the amygdalar-hippocampal complex. 18 We report two siblings with MPSIIIC and severely altered emotional behavior who meet the diagnostic criteria for KBS with onset at MPSIII stage 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Affected children experience progressive neurological deterioration and early death. Work by others showed that behavioral abnormalities in Sanfilippo children with the phenotypically-similar type A include a Klüver-Bucy like syndrome with reduced fearfulness [4,5]. This reduced fear response was found to correlate with volume loss in the amygdala [4].…”
Section: Introductionmentioning
confidence: 99%